A novel non-invasive and echocardiography-derived method for quantification of right ventricular pressure–volume loops. (28th February 2021) - Richter, Manuel J; Yogeswaran, Athiththan; Husain-Syed, Faeq; Vadász, István; Rako, Zvonimir; Mohajerani, Emad; Ghofrani, Hossein A; Naeije, Robert; Seeger, Werner; Herberg, Ulrike; Rieth, Andreas; Tedford, Ryan J; et al.
Abstract: Aims: We sought to assess the feasibility of constructing right ventricular (RV) pressure–volume (PV) loops solely by echocardiography. Methods and results: We performed RV conductance and pressure wire (PW) catheterization with simultaneous echocardiography in 35 patients with pulmonary hypertension. To generate echocardiographic PV loops, a reference RV pressure curve was constructed using pooled PW data from the first 20 patients (initial cohort). Individual pressure curves were then generated by adjusting the reference curve according to RV isovolumic and ejection phase duration and estimated RV systolic pressure. The pressure curves were synchronized with echocardiographic volume curves. We validated the reference curve in the remaining 15 patients (validation cohort). Methods were compared with correlation and Bland–Altman analysis. In the initial cohort, echocardiographic and conductance-derived PV loop parameters were significantly correlated rho = 0.8053 [end-systolic elastance (Ees)], 0.8261 [Ees/arterial elastance (Ea)], and 0.697 (stroke work); all P < 0.001, with low bias [−0.016 mmHg/mL (Ees), 0.1225 (Ees/Ea), and −39.0 mmHg mL (stroke work)] and acceptable limits of agreement. Echocardiographic and PW-derived Ees were also tightly correlated, with low bias (−0.009 mmHg/mL) and small limits of agreement. Echocardiographic and conductance-derived Ees, Ees/Ea, and stroke work were also tightly correlated in the validation cohort (rho = 0.9014, 0.9812, and 0.9491, respectively; all P < 0.001), with low bias (0.0173 mmHg/mL, 0.0153, and 255.1 mmHg mL, respectively) and acceptable limits. Conclusion: The novel echocardiographic method is an acceptable alternative to invasively measured PV loops to assess contractility, RV-arterial coupling, and RV myocardial work. Further validation is warranted.